An analysis of treatment integrity of response interruption and redirection. Issue 2 (15th January 2019) - Colón, Candice L.; Ahearn, William H.
Abstract : Response interruption and redirection has been shown to effectively decrease stereotypy, but its application outside an experimental setting has not been well studied. In Experiment 1, decreases in automatically maintained vocal stereotypy were obtained following treatment in a controlled setting for 3 participants diagnosed with autism spectrum disorder. Descriptive data on the consistency and accuracy of response interruption and redirection were then collected in the classroom setting. Results showed that the consistency of treatment implementation varied across participants and staff members. Failure to implement the treatment was the most common error. However, when response interruption and redirection was implemented, the components were generally carried out as prescribed. In Experiment 2, we conducted a parametric analysis in a controlled setting to test the impact of consistency errors on response interruption and redirection. The results indicated that response interruption and redirection was generally effective at 50% treatment implementation or higher. Furthermore, we observed treatment effects when 25% implementation sessions were interspersed with 100% treatment implementation sessions. Application of response interruption and redirection in light of previous studies and clinical implications are discussed.